Outcome of kidney transplant recipients with a history of hepatitis B and C viruses - Hajar Fitah; Hajar El Allagui; Nabil Hmaidouch; El Galiou Mariam; Naima Ouzeddoun; Loubna Benamar; Tarik Bouattar (REV SEN)
Introducción: Kidney transplantation (KT) in patients with viral hepatitis (HBV and HCV) represents a significant challenge, given its high prevalence and its contribution to important posttransplant complications. The objective of this study is to evaluate the posttransplant evolution of patients who were treated and cured of hepatitis B or C before receiving the transplant.